Self‐organization of apical membrane protein sorting in epithelial cells. (28th April 2021) - Levic, Daniel S.; Bagnat, Michel
Abstract : Polarized epithelial cells are characterized by the asymmetric distribution of proteins between apical and basolateral domains of the plasma membrane. This asymmetry is highly conserved and is fundamental to epithelial cell physiology, development, and homeostasis. How proteins are segregated for apical or basolateral delivery, a process known as sorting, has been the subject of considerable investigation for decades. Despite these efforts, the rules guiding apical sorting are poorly understood and remain controversial. Here, we consider mechanisms of apical membrane protein sorting and argue that they are largely driven by self‐organization and biophysical principles. The preponderance of data to date is consistent with the idea that apical sorting is not ruled by a dedicated protein‐based sorting machinery and relies instead on the concerted effects of oligomerization, phase separation of lipids and proteins in membranes, and pH‐dependent glycan interactions. Abstract : Despite extensive investigation, the mechanisms targeting membrane proteins to the apical surface are not well understood. In this Viewpoint, we survey historical findings and recent advances in membrane protein sorting. We argue that apical sorting, through diverse mechanisms, is organized by biophysical phenomena of cargo segregation driven by oligomerization and phase separation. Evidence suggests that the molecular interactions underlying apical segregation of O ‐glycosylated membrane proteins are regulated by luminal acidification.